2017
DOI: 10.1186/s12943-017-0701-0
|View full text |Cite
|
Sign up to set email alerts
|

Metformin suppresses cancer initiation and progression in genetic mouse models of pancreatic cancer

Abstract: BackgroundPancreatic ductal adenocarcinoma (PDAC) is the fourth leading cause of cancer-associated mortality worldwide with an overall five-year survival rate less than 7%. Accumulating evidence has revealed the cancer preventive and therapeutic effects of metformin, one of the most widely prescribed medications for type 2 diabetes mellitus. However, its role in pancreatic cancer is not fully elucidated. Herein, we aimed to further study the preventive and therapeutic effects of metformin in genetically engine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 105 publications
(84 citation statements)
references
References 52 publications
3
81
0
Order By: Relevance
“…Of note, senescent cells are highly glycolytic (Moiseeva, Bourdeau, Roux, Deschenes‐Simard, & Ferbeyre, ) suggesting that the defects in this pathway observed in cancer stem cells are acquired during tumor progression. Metformin treatment of mice expressing oncogenic Kras in the pancreas delayed tumorigenesis and decreased the percentage of both early and late PanIN lesions (Chen et al, ). Also, metformin has been shown to target selectively breast and pancreatic cancer cells with stem cell properties (Hirsch et al, ; Sancho et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, senescent cells are highly glycolytic (Moiseeva, Bourdeau, Roux, Deschenes‐Simard, & Ferbeyre, ) suggesting that the defects in this pathway observed in cancer stem cells are acquired during tumor progression. Metformin treatment of mice expressing oncogenic Kras in the pancreas delayed tumorigenesis and decreased the percentage of both early and late PanIN lesions (Chen et al, ). Also, metformin has been shown to target selectively breast and pancreatic cancer cells with stem cell properties (Hirsch et al, ; Sancho et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Transgenic pancreatic cancer mouse was introduced as previous described [23]. 20 Kras Pdx1-Cre (KPC) mouse were randomly divided into 2 groups; Control group and SFN treatment group.…”
Section: Transgenic Pancreatic Cancer Mouse and Nude Micementioning
confidence: 99%
“…As the previous study showed, metformin inhibited autophagy induced by gefitinib and vorinostat whose mechanism had not been clear; in this research, the same phenomenon was observed in osimertinib‐treated NSCLC cells, and metformin combined with osimertinib had a synergistic anti‐tumour effect. Studies have found that the effective mechanism of metformin in cancer cells may be due to cell cycle arrest induction, mTOR inhibition, JAK2/STAT signalling inhibition, immunomodulation, cytotoxic properties and autophagy regulation . Despite both metformin and autophagy inhibitor could inhibit the induction of autophagy, metformin may be a better choice of cancer treatment because of its rich mechanism, metformin co‐treatment with osimertinib probably has more clinical efficiency.…”
Section: Discussionmentioning
confidence: 99%